Cascading impacts of bark beetle‐caused tree mortality on coupled biogeophysical and biogeochemical processes. Issue 8 (10th September 2012) - Edburg, Steven L; Hicke, Jeffrey A; Brooks, Paul D; Pendall, Elise G; Ewers, Brent E; Norton, Urszula; Gochis, David; Gutmann, Ethan D; Meddens, Arjan JH
Abstract : Recent, large‐scale outbreaks of bark beetle infestations have affected millions of hectares of forest in western North America, covering an area similar in size to that impacted by fire. Bark beetles kill host trees in affected areas, thereby altering water supply, carbon storage, and nutrient cycling in forests; for example, the timing and amount of snow melt may be substantially modified following bark beetle infestation, which impacts water resources for many western US states. The quality of water from infested forests may also be diminished as a result of increased nutrient export. Understanding the impacts of bark beetle outbreaks on forest ecosystems is therefore important for resource management. Here, we develop a conceptual framework of the impacts on coupled biogeophysical and biogeochemical processes following a mountain pine beetle (Dendroctonus ponderosae ) outbreak in lodgepole pine (Pinus contorta Douglas varlatifolia ) forests in the weeks to decades after an infestation, and highlight future research needs and management implications of this widespread disturbance event.